2011
DOI: 10.1007/s10729-011-9180-9
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of prospective payment on local hospital competition in Germany

Abstract: The introduction of prospective hospital reimbursement based on diagnosis related groups (DRG) in 2004 has been a conspicuous attempt to increase hospital efficiency in the German health sector. As a consequence of the reform a rise of competition for (low cost) patients could be expected. In this paper the competition between hospitals, quantified as spatial spillover estimates of hospital efficiency, is analyzed for periods before and after the reform. We implement a two-stage efficiency model that allows fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 48 publications
(72 reference statements)
0
29
1
3
Order By: Relevance
“…Moreover we were unable to substantiate claims that non-profit and university hospitals achieve more positive results for economic efficiency [63], as the economic results achieved are not unambiguous [64].…”
Section: Discussionmentioning
confidence: 64%
“…Moreover we were unable to substantiate claims that non-profit and university hospitals achieve more positive results for economic efficiency [63], as the economic results achieved are not unambiguous [64].…”
Section: Discussionmentioning
confidence: 64%
“…Competition, which is often related to the introduction of prospective payment systems [1][2][3], has increased among European hospitals in recent decades. Thus, hospitals' strategic behavior, including their strategic positioning and competitive advantage relative to competitors, has become more relevant.…”
Section: Introductionmentioning
confidence: 99%
“…The studies considered either DEA or stochastic frontier approach based on different functions. Linna and Häkkinen [11] and Lee et al [12] show specialization is positively associated with efficiency, also, Herwartz and Strumann [13] demonstrated that the relationship between specialization and efficiency is changed over time.…”
Section: Literature Reviews Of Hospitals Evaluationmentioning
confidence: 99%